Leadership Style, Motivation, and Organizational Culture on Job Satisfaction and Teacher Performance - Lindawati Sirait; Sudarno; Achmad Tavip Junaedi; Astri Ayu Purwati; Mazzlida Mat Deli (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
The purpose of this study was to determine and analyze the influence of leadership style, work motivation, organizational culture on job satisfaction and teacher performance at the Taruna Andalan School of the Kerinci Citra Kasih Foundation. The population of this study were all teachers at the Taruna Andalan School as many as 85 people. While the sample technique used is the saturated sample technique. Where this technique all members of the population are sampled. Based on the sampling technique, the sample of this study was set at 85 samples. The data analysis technique in this study used descriptive analysis and PLS structural equation model (SEM) analysis. The results of this study indicate that leadership style, work motivation, organizational culture have a positive and significant impact on teacher job satisfaction. Leadership style, job satisfaction have a positive and significant impact on performance. Meanwhile, work motivation and organizational culture are not significant on performance. The results of the intervening research are very interesting to study further because the variables that have an influence tend to be related to the characteristics of the teachers at the Taruna Andalan School. Leadership style, work motivation and organizational culture have no significant effect on teacher performance. For further researchers, it is expected to replace other variables if they want to examine the same object.